2022
DOI: 10.1186/s13052-022-01347-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical analysis of bronchoscope diagnosis and treatment for airway foreign body removal in pediatric patients

Abstract: Background Along with the wide spread application and technical development of the flexible and rigid bronchoscopy, the airway foreign body removing method cme to the specific technique for different foreign bodies from the single foreign body forceps. Methods Selected 633 children who were diagnosed as airway foreign bodies by the Department of Respiratory Intervention, Children's Hospital affiliated to Shandong University from January 1st, 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Many studies have reported the safe use of bronchoscopy in neonates (15,21,27,30). In this study, the most common complications were hypoxemia (17.6%) and airway mucosal hemorrhage (14.3%).…”
Section: Discussionmentioning
confidence: 74%
“…Many studies have reported the safe use of bronchoscopy in neonates (15,21,27,30). In this study, the most common complications were hypoxemia (17.6%) and airway mucosal hemorrhage (14.3%).…”
Section: Discussionmentioning
confidence: 74%
“…Recently, however, more studies have been published that report significantly better success rates for FBR by FB. In 2022, Han et al [34 ▪▪ ] published their experience with FB for FBR in 633 patients with a success rate of 99.2%. Only in five cases (0.8%) was a combination with rigid bronchoscopy needed.…”
Section: Bronchoscopic Techniquesmentioning
confidence: 99%
“…Failure to promptly address this situation may give rise to life-threatening repercussions. Preventing complications or mortality in early pregnancy requires promptly using bronchoscopy for FB removal [ 1 ]. Recently, flexible bronchoscopy has emerged as a prevalent and widely adopted approach for the extraction of foreign bodies [ 2 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxemia is one of the most common adverse events during both flexible bronchoscopy and rigid bronchoscopy. Hypoxic arrest is the primary cause of death during bronchoscopy [ 1 ]. Rapid desaturation causes cardiac arrest at a rate of up to 0.36% 5 .…”
Section: Introductionmentioning
confidence: 99%